Of maps, cartography and the geography of the International Cartographic Association - Fabrikant, S.I. (2020)
In this contribution, we first focus on maps as landmarks of cartographic innovation in the context of societal and technical developments in history. We then turn to cartography itself, by analyzing the sustainability of past and current disciplinary definitions, as proposed by its leading professional body, the International Cartographic Association (ICA). In the fourth section, we then go on to analyze the structure and activities of the ICA over the recent past, with the aim to further understand the professional development of the cartographic discipline. Finally, we also consider how the geography of the ICA.